Determination of Zirconium and Titanium in Marine Placer Deposits by ICP-OES with Alkali Fusion of Lithium Metaborate-Lithium Tetraborate Composite Flux - Yijun ZHANG; Yuhang ZHANG; Yan CHEN; Yan DENG; Jiahan WANG (Yankuang ceshi)
The marine placer deposits of Hainan Island contain abundant zirconium (Zr) and titanium (Ti) resources, which hold significant development potential. An alkali fusion-inductively coupled plasma-optical emission spectrometry method based on a composite flux of lithium metaborate and lithium tetraborate (m∶m=33∶67) was developed for determining Zr and Ti in marine placers. In this method, the sample was fused with 0.8g flux at 1000℃ for 15min. After cooling, the molten substance was poured into a dilute acid and dissolved by oscillation in a constant temperature oscillator. This approach simplifies the operation process by avoiding the complexity associated with high-temperature procedures while enhancing melt dissolution techniques. The detection limit for Zr in this method is 0.40μg/g while that for TiO2 is 0.0025%. Based on standard materials, the relative standard deviation (RSD) of Zr ranges between 1.0%−3.5%; RSD of TiO2 ranges between 0.7%−3.3%. These precision values align with quality management standards set forth by geological and mineral laboratory testing. The method is suitable for rapid continuous analysis of Zr and Ti in marine placer deposits.